Peran Akuntansi Badan Layanan Umum Terhadap Pengelolaan Keuangan (Studi Literatur) - Putri, Wan Raudhatuk Jannah Syah; Rizkiani, Dianti; Sari, Eka Nurmala (Jurnal Riset AKuntansi dan Bisnis, 2025)
This research aims to review articles related to Public Service Agency Accounting. This research method uses SLR (Systematic Literature Review) where article sources are taken from several data bases in order to obtain data that matches the title of this article. Data retrieval sources come from searches of national and international journals published on Google Scholar, via the publish or application. peris. The results of the analysis using VosViewer on network visualization, overlay visualization, and density visualization show the relationship between various concepts related to Public Service Agency AccountingThis research aims to review articles related to Public Service Agency Accounting. This research method uses SLR (Systematic Literature Review) where article sources are taken from several data bases in order to obtain data that matches the title of this article. Data retrieval sources come from searches of national and international journals published on Google Scholar, via the publish or application. peris. The results of the analysis using VosViewer on network visualization, overlay visualization, and density visualization show the relationship between various concepts related to Public Service Agency Accounting